A sociedade contemporânea: o brincar e o brinquedo - Lengyel, Andréa Nosek (2012)
This paper intends to discuss current forms of children s play, toys and games used in contemporary society, under a psychoanalytical perspective. Considering contemporary society as a consumer s society, under the influence of advertising and television, resulting in a culture of image and spectacle. Alongside peremptory happiness and immediatism, there is a requirement of fulfillment and competency directing people s lives, including children s. The new social logic assigns people hierarchically according to consumption possibilities: those who are or are not; who can or cannot; who have or do not have worth. As a result, depriving them of the right to autheticity and freedom since childhood. The rules are given and we try to adapt to them. As the psychoanalytical basis for this paper, I used the support of Sigmund Freud s, D. W. Winnicott s and J. Lacan s works. In the transition from a modern production society to a post-modern consumption society, I approach the subject who seeks completeness by acquiring goods, thus obliterating their own possibility to desire, play and fantasize. In the Capitalistic ideal, it is imperative to shorten the path between production and consumption. To illustrate this cultural change, I analyzed children s play and today s predominant birthday parties model, which I then compare to other more traditional forms of celebration. Moreover, I comment on the intensity of stimuli intended to entertain, motivate and teach children, but which ignore their capacities to choose, think, create, and, mostly, desire